Antituberculosis Therapy and Gut Microbiota: Review of Potential Host Microbiota Directed-Therapies - Diallo, Dramane; Somboro, Anou M.; Diabate, Seydou; Baya, Bacar; Kone, Amadou; Sarro, Yeya S.; Kone, Bourahima; Diarra, Bassirou; Diallo, Souleymane; Diakite, Mahamadou; Doumbia, Seydou; Toloba, Yacouba; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Tuberculosis (TB) remains a major public health concern with millions of deaths every year. The overlap with HIV infections, long treatment duration, and the emergence of drug resistance are significant obstacles to the control of the disease. Indeed, the standard first-line regimen TB treatment takes at least six months and even longer for the second-line therapy, resulting in relapses, drug resistance and re-infections. Many recent reports have also shown prolonged and significant damage of the gut microbial community (dysbiosis) from anti-TB drugs that can detrimentally persist several months after the cessation of treatment and could lead to the impairment of the immune response, and thus re-infections and drug resistance. A proposed strategy for shortening the treatment duration is thus to apply corrective measures to the dysbiosis for a faster bacterial clearance and a better treatment outcome. In this review, we will study the role of the gut microbiota in both TB infection and treatment, and its potential link with treatment duration. We will also discuss, the new concept of “Host Microbiota Directed-Therapies (HMDT)” as a potential adjunctive strategy to improve the treatment effectiveness, reduce its duration and or prevent relapses. These strategies include the use of probiotics, prebiotics, gut microbiota transfer, and other strategies. Application of this innovative solution could lead to HMDT as an adjunctive tool to shorten TB treatment, which will have enormous public health impacts for the End TB Strategy worldwide.